2022
DOI: 10.21037/apm-21-1510
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-rich plasma combined with ozone prevents cartilage destruction and improves weight-bearing asymmetry in a surgery-induced osteoarthritis rabbit model

Abstract: Background: Osteoarthritis (OA) is the most common degenerative disease in older adults and its treatment remains unsatisfactory. This study aimed to evaluate the effectiveness and explore the therapeutic mechanisms of the combination of platelet-rich plasma (PRP) and ozone (O 3 ) for knee OA.Methods: Thirty male rabbits were randomly divided into five groups (Control group, OA group, PRP group, O 3 group, and PRP + O 3 group). Rabbit model of OA were induced by improved Hulth surgery.Gross articular observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Animal model studies have reported that IAI of ozone induced a decrease in TNF-α, IL-1β, and IL-6 levels, as well as a decrease in intra-articular oxidative stress regulation, without generating cartilage toxicity 35,36 ; in addition, it has been reported that IAI of ozone decreases the expression of matrix metalloproteinase 1 (MMP-1) and bone morphogenetic protein 2 compared with controls. 37 These results have been reproduced in humans. Hashemi et al 38 reported a decrease in serum levels of IL-1β and TNF-α in patients with KOA treated using IAI of ozone, without differences at 1 month of follow-up when compared with IAI of CSs.…”
Section: Intra-articular Injections Under Study Intra-articular Injec...mentioning
confidence: 63%
See 1 more Smart Citation
“…Animal model studies have reported that IAI of ozone induced a decrease in TNF-α, IL-1β, and IL-6 levels, as well as a decrease in intra-articular oxidative stress regulation, without generating cartilage toxicity 35,36 ; in addition, it has been reported that IAI of ozone decreases the expression of matrix metalloproteinase 1 (MMP-1) and bone morphogenetic protein 2 compared with controls. 37 These results have been reproduced in humans. Hashemi et al 38 reported a decrease in serum levels of IL-1β and TNF-α in patients with KOA treated using IAI of ozone, without differences at 1 month of follow-up when compared with IAI of CSs.…”
Section: Intra-articular Injections Under Study Intra-articular Injec...mentioning
confidence: 63%
“…Although the scientific bases to support its clinical use are not entirely clear, there is positive preclinical and clinical evidence on the mechanisms of action and the efficacy and safety of this intervention. Animal model studies have reported that IAI of ozone induced a decrease in TNF-α, IL-1β, and IL-6 levels, as well as a decrease in intra-articular oxidative stress regulation, without generating cartilage toxicity 35,36 ; in addition, it has been reported that IAI of ozone decreases the expression of matrix metalloproteinase 1 (MMP-1) and bone morphogenetic protein 2 compared with controls 37 . These results have been reproduced in humans.…”
Section: Intra-articular Injections Under Studymentioning
confidence: 91%
“…Recently, research on the combination of ozone and PRP is most prevalent in the fields of orthopedics and sports medicine, with promising outcomes [ [18] , [19] , [20] ]. Studies indicate that ozone can enhance the expression of some GFs in PRP which play a crucial role in skin tissue remodeling [ 21 ], but the role of ozone in enhancing the concentration of GFs in PRP in facial injections has not been studied yet.…”
Section: Introductionmentioning
confidence: 99%